2019
DOI: 10.3201/eid2509.190587
|View full text |Cite
|
Sign up to set email alerts
|

Blastomycosis Misdiagnosed as Tuberculosis, India

Abstract: Chronic pulmonary blastomycosis is often misdiagnosed and treated as tuberculosis in disease-endemic and non–disease-endemic areas. We report the case of a 32-year-old man who after visiting Chicago, Illinois, USA, returned to India and received treatment for tuberculosis for 12 months before receiving the correct diagnosis of blastomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In fact, EPTB can show a variety of symptoms, which may be similar to those of other diseases such as lymphomas, solid tumours and infectious diseases. This brings further challenge to diagnosis of EPTB [9][10]. Therefore, clinicians need to consider the possibility of EPTB as a differential diagnosis.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…In fact, EPTB can show a variety of symptoms, which may be similar to those of other diseases such as lymphomas, solid tumours and infectious diseases. This brings further challenge to diagnosis of EPTB [9][10]. Therefore, clinicians need to consider the possibility of EPTB as a differential diagnosis.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…However, pathogens that survived initial immune assaults can persist and replicate in macrophages. 85,86 These intracellular infections cause pulmonary infiltrate with granulomas, accompanying necrosis and fibrosis in adjacent tissues. 87,88 Although B. dermatitidis and M. tuberculosis are sequestered in granulomas, these microbes can be reactivated by dysregulation of host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Anil kumar et al, reported a similar case where a 32-year-old man who returned to India after visiting Chicago, Illinois, and was treated for TB for 12 months before being diagnosed with blastomycosis [5]. Matthew et al, also reported a similar case where year old male from Mississippi river valley with complaints of haemoptysis, fatigue, weight loss, and fever and CT chest showing a large cavitary lesion in the right upper lobe.…”
Section: Journal Of Case Reports and Studiesmentioning
confidence: 98%